Desain Pemanfaatan Sel Surya sebagai Energi Alternatif Bahan Bakar Solar pada Perahu Wisata di Pantai Lovina Bali - Apriansyah Apriansyah; Ni Wayan Elmy Diahutari (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
Lovina Beach, which is located in Buleleng Regency, Bali Province, is very attractive to tourists because it presents the attraction of wild dolphins in the middle of the sea. The dolphins on Lovina Beach are protected by local government regulations, so no one is allowed to catch or sell them. To be able to watch dolphin attractions in the middle of the sea, tourists must rent a boat that has been provided by the manager. Boats that sail using diesel fuel are quite expensive. These conditions are the background to serve this article. We develop solar cells as an alternative energy fuel for boat propulsion. Solar cell is a device or component that can convert sunlight energy into electrical energy using the Photovoltaic effect principle. The photovoltaic effect is an earthquake phenomenon where the voltage is due to the contact or contact of two electrodes which are served with a solid or liquid system when receiving light energy. The electrical energy that is processed is stored in the battery which will be used while sailing. The advantage of solar cells is that they are environmentally friendly and do not cause pollution at all, and solar cells are a source of energy considering their sustainable nature (renewable) and abundant instructions. Keywords: Boat, diesel fuel, solar cells.